Используя формулу умножения (где это возможно), выражение: a) (4x ^ 2 + 3x-6) + (x ^ 3 + 5x ^ 2-6x + 10), b) (x-2y) ^ 2 + 4 (4y + 5x), c) (a-3b) (a + 3b) - (a ^ 2 + 6b ^ 2).

gatilovasofiya gatilovasofiya    1   28.09.2019 09:20    0

Ответы
приветпомогипж2 приветпомогипж2  09.10.2020 00:22
А)

(4x² + 3x - 6) + (x³ + 5x² - 6x + 10) = 4x² + 3x - 6 + x³ + 5x² - 6x + 10 =

= x³ + 9x² - 3x + 4

б)

(x - 2y) ² + 4 (4y + 5x) = x² - 4xy + 4y² + 16y + 20x = x² - 4xy + 20x + 4y² + 16y

с)

(a - 3b) (a + 3b) - (a² + 6b²) = a² - 9b² - a² - 6b² = -15b²
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика